Treatment of dry Skin syndrome : the art and science of moisturizers - Maibach, Howard I.; Loden, Marie (Springer Berlin Heidelberg, 2012)
Dry skin impacts on the lives of many individuals but in most cases it can be adequately managed with current moisturizing products. Certain moisturizers, however, can themselves adversely affect the quality of life by inducing further dryness and eczema and so becoming addictive. In addition, there is a possible link between moisturizing treatments and asthma. Development of moisturizers is a scientific and artistic discipline, where consumer insights are also needed. This new book bridges the gap between the moisturizers and the skin by covering all the essential information required to tailor the use of moisturizers to particular disorders and patients. Important aspects of skin biochemistry and barrier function are explained, and the ingredients and treatment effects of moisturizers are explored in depth. Careful attention is paid to controversies, including the role of certain moisturizers in inducing dryness/eczema, asthma, and comedones. The information provided in this unique book will enable the reader to go beyond the traditional thinking regarding skin care. The novel insights offered will suggest the properties required for a new generation of moisturizing treatments that more effectively improve the quality of life.